The Rhyacophila fasciata Group in Croatia and Bosnia and Herzegovina: Rhyacophila f. fasciata Hagen 1859 and the description of two new subspecies, Rhyacophila fasciata delici Kučinić & Valladolid (ssp. nov.) from Croatia and Bosnia and Herzegovina and Rhyacophila fasciata viteceki Valladolid & Kučinić (ssp. nov.) from Bosnia and Herzegovina (Trichoptera: Rhyacophilidae) - Valladolid, María; Kučinić, Mladen; Arauzo, Mercedes; Cerjanec, Darko; Ćuk, Renata; Dorda, Beatriz A.; Lodovici, Omar; Stanić-Koštroman, Svjetlana; Vučković, Ivan; Rey, Isabel (Zootaxa, 2020)
We present the description of two new subspecies of the Rhyacophila fasciata Group: Rhyacophila fasciata delici Kučinić & Valladolid (ssp. nov.), broadly distributed in Croatia and present also in Bosnia and Herzegovina, and R. fasciata viteceki Valladolid & Kučinić (ssp. nov.), found in Bosnia and Herzegovina. Our study of the morphology of adults, as well as our analysis of the barcode region of the mitochondrial cytochrome oxidase I (mtCOI) gene and geographical distribution confirm the differences of the two new subspecies with the nominal species R. f. fasciata, also found in both countries.